Relation of Learning Compass 2030 and Management Regulation of Merdeka Curriculum for School and Higher Education in Indonesia - Fitriza, Zonalia; Wahyudin, Dinn; Dewi, Laksmi (Journal of Disruptive Learning Innovation (JODLI), 2023)
Technological developments and global competition are challenges in this digital era that require Indonesia’s young generation preparing themselves to compete in this disruptive era. The Merdeka Curriculum (Freedom to Learn) at Schools and the Merdeka Belajar Kampus Merdeka (MBKM) Curriculum (Freedom to Learn) at Universities in Indonesia are implemented to prepare students to have future competencies consisting of knowledge, skills, attitudes, and values which are called as the 2030 Learning Compass. This study aims to describe the relationship between the Management policies of Merdeka and the MBKM curriculum with Learning Compass 2030. Eight policy documents related to the management of the aforementioned curriculum were analyzed through the document analysis method with an interpretive approach to reveal how the latest curriculum management policies can achieve the goals of Learning Compass 2030. The results obtained are regulations issued by the Indonesian government regarding curriculum management possibly achieving competencies consisting of knowledge, skills, attitudes, and values if planning, implementing, evaluating, and controlling are in ideal condition.